Beyond Menstrual Dysfunction : Does Altered Endocrine Function Caused by Problematic Low Energy Availability Impair Health and Sports Performance in Female Athletes? - Ihalainen, Johanna K.; Mikkonen, Ritva S.; Ackerman, Kathryn E.; Heikura, Ida A.; Mjøsund, Katja; Valtonen, Maarit; Hackney, Anthony C. (Adis, 2025)
Low energy availability, particularly when problematic (i.e., prolonged and/or severe), has numerous negative consequences for health and sports performance as characterized in relative energy deficiency in sport. These consequences may be driven by disturbances in endocrine function, although scientific evidence clearly linking endocrine dysfunction to decreased sports performance and blunted or diminished training adaptations is limited. We describe how low energy availability-induced changes in sex hormones manifest as menstrual dysfunction and accompanying hormonal dysfunction in other endocrine axes that lead to adverse health outcomes, including negative bone health, impaired metabolic activity, undesired outcomes for body composition, altered immune response, problematic cardiovascular outcomes, iron deficiency, as well as impaired endurance performance and force production, all of which ultimately may influence athlete health and performance. Where identifiable menstrual dysfunction indicates hypothalamic-pituitary-ovarian axis dysfunction, concomitant disturbances in other hormonal axes and their impact on the athlete's health and sports performance must be recognized as well. Given that the margin between podium positions and "losing" in competitive sports can be very small, several important questions regarding low energy availability, endocrinology, and the mechanisms behind impaired training adaptations and sports performance have yet to be explored.